Minds and gods the cognitive foundations of religion - Tremlin, Todd.; Oxford eBooks (New York ; Oxford : Oxford University Press, 2006)
This volume explains the origins and persistence of religious ideas on the basis of common structures and functions of human thought. It describes the evolutionary forces that molded the modern human mind. It details many adapted features of the brain, illustrating their operation with examples of everyday human behavior.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Psychology, Religious; Psychology and religion; Evolutionary psychology; Thought and thinking -- Religious aspects; Faith; Electronic books